Design And Optimization Of Front Lower Control Arm (FLCA) For C-Segment Passenger Car - Salleh, Mohd Shukor; Abdul Rahman, Mohd Hafizi; Ab. Razak, Mohd Suffian; Mohamad Kamal, Mohamad Ridzuan; Marjom, Zolkarnain; Anuar, Liza; Mohamad Saad, Nur Adzly (Science Publishing Corporation, 2018)
In this paper,the design optimization and fabrication process of aluminium cast for front lower control arm (FLCA) were investigated.In this work,the new design concept of front lower control arm is employed.CATIA software was employed in this work to design the concept of the lower control arm.After that,Hyperworks software is used to analyze the structural strength and optimized the weight of the part.The target of the new design is 20% reduction of the overall weight of the front lower control arm which fabricated using steel material.The obtained results show a significant reduction of the overall weight as high as 25% with a fatigue life cycle 396,000 cycles.This finding proved that the new design of front lower arm has fulfilled the criteria of fatigue life cycle and suitable to be used in a C-segment passenger car.